Cost-Effectiveness of Transcatheter Versus Surgical Aortic Valve Replacement in Patients With Severe Aortic Stenosis at Intermediate Risk: Results From the PARTNER 2 Trial. Issue 7 (12th February 2019) - Baron, Suzanne J.; Wang, Kaijun; House, John A.; Magnuson, Elizabeth A.; Reynolds, Matthew R.; Makkar, Raj; Herrmann, Howard C.; Kodali, Susheel; Thourani, Vinod H.; Kapadia, Samir; Svensson, Lars; Mack, Michael J.; et al.
Abstract : Background: In patients with severe aortic stenosis (AS) at intermediate surgical risk, treatment with transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (SAVR) results in similar rates of death or stroke at 2 years. Whether TAVR is cost-effective compared with SAVR for intermediate-risk patients remains uncertain. Methods: Between 2011 and 2014, 3110 intermediate-risk AS patients were treated with TAVR or SAVR in the PARTNER 2 trial (Placement of Aortic Transcatheter Valves 2). A total of 2032 patients were randomized to receive TAVR using the SAPIEN XT valve (XT-TAVR) or SAVR in the PARTNER 2A trial, whereas the PARTNER S3i registry included an additional 1078 patients treated with TAVR using the SAPIEN 3 valve (S3-TAVR), which offers a lower delivery profile and sealing skirt designed to reduce paravalvular regurgitation compared with XT-TAVR. Procedural costs were estimated using measured resource utilization. Other in-trial costs were assessed by linkage of trial data with Medicare claims (n=2333) or by linear regression models for unlinked patients (n=682). Health utilities were estimated using the EQ-5D at baseline and 1, 12, and 24 months. Using a Markov model informed by in-trial costs, utilities, and survival data, lifetime cost-effectiveness from the perspective of the US healthcare system was estimated in terms of cost per quality-adjusted life-year gained. Results: Although procedural costs were ≈$20 000 higher with TAVR than SAVR, total cost differences for the index hospitalization were only $2888 higher with XT-TAVR ( P =0.014) and were $4155 lower with S3-TAVR ( P <0.001) owing to reductions in length of stay with TAVR. Follow-up costs were significantly lower with XT-TAVR (Δ=−$9304; P <0.001) and S3-TAVR (Δ=−$11 377; P <0.001) than with SAVR. Over a lifetime horizon, TAVR was projected to lower total costs by $8000 to $10 000 and to increase quality-adjusted survival by 0.15 to 0.27 years. XT-TAVR and S3-TAVR were found to be economically dominant compared with SAVR in 84% and 97% of bootstrap replicates, respectively. Conclusions: Among intermediate-risk AS patients, TAVR is projected to be economically dominant from the perspective of the US healthcare system by providing both greater quality-adjusted life expectancy and lower long-term costs than SAVR. If long-term data demonstrate comparable late mortality with TAVR and SAVR, these findings suggest that TAVR might be the preferred treatment strategy for intermediate-risk AS patients based on both clinical and economic considerations. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01314313. Abstract : Supplemental Digital Content is available in the text.